The livelihood approach: a critical exploration - de Haan, Leo (ERDKUNDE, 2012)
The livelihood approach is an important actor-oriented perspective in development studies, including geography of development, which strongly influenced development oriented research and development practice. This paper deals with the original outlines of that approach and its subsequent critique and evolution. It discusses the basics of the original livelihood approach in its development cooperation context around the turn of the millennium. Both its broader popularity in academic research and the initial critique it met are explained. The neglect of power relations was an important flaw of the initial livelihood approach. The paper demonstrates how the following generation of livelihood studies managed to come to grip with that shortcoming and how it developed an understanding of the operation of power in livelihood strategies that can effectively contribute to livelihood enhancement. Finally, this paper criticises current livelihood research for limiting itself to the production of series of studies presenting almost endless variations of local livelihoods. The paper argues for the rise of another type of livelihood studies, which aims – through meta-analysis of the multitude of livelihood studies available and through comparative research – at broader generalisations that may challenge existing theories.